Genetic Quality Improvement of Beef Cattle in Indonesia: Overview and Prospects - Rahmatillah, Ririn Siti; Rahmat, Dedi; Dudi, Dudi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
Technology for Improving the genetic quality of beef cattle is a key factor in the development of the livestock industry in Indonesia. In recent decades, efforts have been made to improve beef cattle’s genetic quality through breeding and modern reproductive technologies. The journal aims to present an in-depth understanding of the efforts made to improve the genetic quality of beef cattle in Indonesia and to explain prospects in terms of breeding and reproductive technology. This article is based on reflections on recent literature and research in this field..